Neuroprotective Effects of N-acetylserotonin and Its Derivative. (1st May 2023) - Kang, Ji-He; Guo, Xu-Dong; Wang, Yi-Dian; Kang, Xue-Wen
Highlights: NAS and HIOC are neuroprotective agents. NAS and HIOC are anti-oxidative stress and anti-inflammatory. NAS and HIOC counteract autophagy dysfunction and apoptosis. NAS and HIOC may show usefulness in clinical trials. Abstract: N-acetylserotonin (NAS) is a chemical intermediate in melatonin biosynthesis. NAS and its derivative N-(2-(5-hydroxy-1H-indol-3-yl) ethyl)-2-oxopiperidine-3-carboxamide (HIOC) are potential therapeutic agents for traumatic brain injury, autoimmune encephalomyelitis, hypoxic-ischemic encephalopathy, and other diseases. Evidence shows that NAS and its derivative HIOC have neuroprotective properties, and can exert neuroprotective effects by inhibiting oxidative stress, anti-apoptosis, regulating autophagy dysfunction, and anti-inflammatory. In this review, we discussed the neuroprotective effects and related mechanisms of NAS and its derivative HIOC to provide a reference for follow-up research and applications.